Murabahah accounting in BNI Syariah Makassar - Firman Manne; Muh. Idris; Erni Erni (Indonesia Prime, 2017)
This research aims to know and analysis implementation of murabahah accounting especially of manifestation murabaha accounting in BNI Syariah. Design methodology used comparative analysis between accounting theory and practice in Syariah banking.The result showed that the implementation of murabahah accounting on BNI Syariah Makassar has been suitable with PSAK 102 especially for recognition, measurement, recording, and disclosure, except for accounting treatment when event of arrears and receipts of arrears installments. BNI Syariah Makassar didn’t give any accounting treatment. Whereas in PSAK 102 is stipulated that when there is arrears and receipts of arrear installments, the margin is recognized proportional to the cash received